New Frontiers in the Intrarenal Renin-Angiotensin System: A Critical Review of Classical and New Paradigms - Zhuo, Jia L.; Ferrao, Fernanda M.; Zheng, Yun; Li, Xiao C. (Frontiers in Endocrinology, 2013)
The renin-angiotensin system (RAS) is well recognized as one of the oldest and most important regulators of arterial blood pressure, cardiovascular and renal function. New frontiers have recently emerged in the RAS research well beyond its classic paradigm as a potent vasoconstrictor, an aldosterone release stimulator, or a sodium-retaining hormone. First, two new members of the RAS have been uncovered, which include the renin/(Pro)renin receptor (PRR) and angiotensin-converting enzyme 2 (ACE2). Recent studies suggest that prorenin may act on the PRR independent of the classical ACE/ANG II/AT1 receptor axis, whereas ACE2 may degrade ANG II to generate ANG (1-7), which activates the Mas receptor. Second, there is increasing evidence that ANG II may function as an intracellular peptide to activate intracellular and/or nuclear receptors. Third, currently there is a debate on the relative contribution of systemic versus intrarenal RAS to the physiological regulation of blood pressure and the development of hypertension. The objectives of this article are to review and discuss the new insights and perspectives derived from recent studies using novel transgenic mice that either overexpress or are deficient of one key enzyme, ANG peptide, or receptor of the RAS. This information may help us better understand how ANG II acts, both independently or through interactions with other members of the system, to regulate the kidney function and blood pressure in health and disease.